CREATING AND MANAGING SQL DATABASES - Ulmaskhujayev Z.; Djuraeva Sh.,; Djuraeva Sh.,; Zokirova F.R. (Journals Park Publishing, 2023)
Currently, SQL (Structured Query Language) is the structured query language. In particular, SQL is a data partitioning language because the database management system also has other language tools. When creating SQL, it was noted that a relational database, close to simple natural language, was designed as a query language, and the article explains its content in more detail.
Keywords: Link, value, block, expression, relational, database, SQL language, database elements, domain creation.